Synthesis, characterization, and in vitro toxicity evaluation of upconversion luminescence NaLuF4:Yb3+/Tm3+ nanoparticles suitable for medical applications. Issue 5 (12th November 2019) - Asadi, Mohammad; Ghahari, Mehdi; Hassanzadeh‐Tabrizi, Seyed A.; Arabi, Amir M.; Nasiri, Rozita
Abstract: Synthesis, characterization, and in vitro toxicity evaluation of upconversion luminescence NaLuF4 :Yb 3+ /Tm 3+ nanoparticles (UCLNPs) are reported in the current study. Initially, the synthesized lanthanide trifluoroacetate (Ln(OOCCF3 )3 ) precursor was used to fabricate NaLuF4 nanoparticles doped with Yb 3+ and Tm 3+ metal ions. The nanoparticles were coated with calcium carbonate (CaCO3 ) after removing the hydrophobic species on them to enhance their biocompatibility. The in vitro methylthiazolyldiphenyl‐tetrazoliumbromide (MTT) test was used to evaluate the toxicity of synthesized NaLuF4 :Yb 3+ /Tm 3+ nanoparticles (NLF‐5) on L929 mouse fibroblast cell lines. The transmission electron microscopy image showed that the particle size of NaLuF4 :Yb 3+ /Tm 3+ was 32 nm. The synthesized NLF‐5 nanoparticles have both α‐cubic and β‐hexagonal crystalline structures that provided a superb near‐infrared‐to‐near‐infrared upconversion luminescence signal when excited at 980 nm. MTT test results show that the death of L929 fibroblast cells was observed only at concentrations above 250 μg/mL of NaLuF4 :Yb 3+ /Tm 3+ nanoparticles. In addition, with an increase in patrol time of 24, 48, and 72 hr, cell toxicity increased significantly, while the coated nanoparticles did not have any toxic effects. The synthesized nanoparticles could be used as a suitable material for medical applications due to their small particle size, high photoluminescence emission intensity, and low toxicity. Abstract : In this manuscript, the authors synthesized NaLuF4:Yb 3+ /Tm 3+ nanoparticles and subsequently coated the nanoparticles with CaCO3 for investigation of their cytotoxicity. Then, the effect of uncoated and coated nanoparticles on the biocompatibility of the MTT test was assessed. In addition, evaluation of the morphological changes and cell death from an inverse optical microscope was evaluated. Besides, the studies related to cell biocompatibility on fibroblast cell lines indicated that there was cytotoxicity in the uncoated sample with a concentration of up to 250 μg/ml.